Communication of adults with moderate in-tellectual disability in the process of auton-omisation – preliminary considerations. - Gawlik, Ewa (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
The aim of this paper is to look into communication in adults with moderate intellectual disability in the process of their autonomisation. This matter has been investigated to shed some light on how people with intellectual disabilities communicate in their social realities in the context of their autonomy and independence. The paper presents a preliminary research using the interpretative paradigm. To deliver the intended goal, the author has used the problem-centered interview.